2022
DOI: 10.1542/peds.2022-056971
|View full text |Cite
|
Sign up to set email alerts
|

Racism and Quality of Neonatal Intensive Care: Voices of Black Mothers

Abstract: BACKGROUND AND OBJECTIVES: Black preterm infants are more likely to die than White preterm infants within the same NICU. Racism may lead to disparate quality of NICU care contributing to disparities in preterm infant health outcomes. The objective of our study was to understand Black mothers’ perspectives of the impact of racism on the quality of care for Black preterm infants in the NICU and what might be done to address it. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…18,19 In a recent qualitative study, Black mothers reported experiencing racism in the NICU at all levels (eg, structural, institutional, and interpersonal) and believe that it impacted the quality of care their infant received. 20 Families report feeling as though nurses disliked them, particularly when that dislike was perceived to be socioeconomically or racially motivated. 21 Fathers generally do not feel included in the care of their hospitalized infants, and Black fathers felt further excluded or unwelcome.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 In a recent qualitative study, Black mothers reported experiencing racism in the NICU at all levels (eg, structural, institutional, and interpersonal) and believe that it impacted the quality of care their infant received. 20 Families report feeling as though nurses disliked them, particularly when that dislike was perceived to be socioeconomically or racially motivated. 21 Fathers generally do not feel included in the care of their hospitalized infants, and Black fathers felt further excluded or unwelcome.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Furthermore, recent literature documents that families from underrepresented backgrounds and groups experience discrimination, racism, and disrespect in healthcare encounters 18,19. In a recent qualitative study, Black mothers reported experiencing racism in the NICU at all levels (eg, structural, institutional, and interpersonal) and believe that it impacted the quality of care their infant received 20. Families report feeling as though nurses disliked them, particularly when that dislike was perceived to be socioeconomically or racially motivated 21.…”
Section: Background and Significancementioning
confidence: 99%
“…In addition to the medical complications faced by patients who have SCD, there are additional elements of racism, bias, and discrimination embedded in clinical encounters leading to miscommunication, bias, and imbalances of power. [4][5][6][7] This can manifest as clinicians viewing patients' expression of pain with skepticism, especially if they do not "look" like they are in pain or have been in the hospital frequently for pain crises.…”
Section: Drs Madni and Aurora Physicians Who Care For Children With Scdmentioning
confidence: 99%
“…10 Awareness,identification, and incorporation of actionable strategies to address bias and the health disparities they contribute to are particularly important in the neonatal intensive care unit (NICU), where IB and HD affect both infants and their families. 11 Black birthing persons…”
Section: Introductionmentioning
confidence: 99%